Program Pengembangan Kurikulum Aqidah Akhlak - Mahmudah, Safira Rona; Ichsan, Yazida; Fauziyah, Nureza; Huda, Ahmat Miftakul (ANWARUL, 2021)
This article discusses moral aqidah education which is a good medium to guide students to get good morals. In the world of education, there are always changes such as changes in the curriculum that develops. The development of the moral aqidah education curriculum does not only occur in the classroom but also in activities outside the classroom such as extracurricular activities. This article aims to find out that curriculum development programs through extracurricular activities are able to overcome the moral crisis, so that they can become Muslim human beings who develop and can improve the quality and piety of Allah SWT, and have noble character in carrying out daily life. The method used in this article uses qualitative research methods with the type of library research. The data collection technique used descriptive data analysis in the form of written data. Based on the article, it can be said that the moral crisis can be overcome through moral aqidah education by developing a curriculum, namely carrying out Islamic extracurricular activities.